Permasalahan Yuridis Penentuan Pelaku Utama Dalam Pemberian Justice Collaborator Sebuah Tindak Pidana Tertentu - Harahap, Mar’ie Mahfudz; Anwar, Reski Reski (Fakultas Hukum Universitas Bangka Belitung, 2022)
Abstract Justice collaborators are very much needed by law enforcement in uncovering certain criminal acts. The fact is that in the formulation of the justice collaborator arrangement in the law, especially the problem of determining the main actor, there are still many juridical problems that have an impact on its application and implementation. This research is classified into normative legal research (normative juridical), using primary legal materials and secondary legal materials. The approach used is a statutory approach to review all relevant rules and regulations. In this study, we will discuss the problem of legal arrangements related to the provisions for determining the provision of a justice collaborator for a particular crime, and the juridical problem of determining the main actor in the provision of a justice collaborator for a particular crime. The findings in this study indicate that there is no juridical definition of the main actors who cause legal problems at the level of norms and practice. The next finding is the difference in perception and the unclear determination of authority to determine the main actors between law enforcers which results in legal uncertainty. Keywords: Juridical Problems, Main Actor, Justice Collaborator, Certain Criminal acts.